2009
DOI: 10.1002/adma.200900956
|View full text |Cite
|
Sign up to set email alerts
|

Electronic and Mechanical Coupling in Bent ZnO Nanowires

Abstract: A red shift of the exciton of ZnO nanowires is efficiently produced by bending strain, as demonstrated by a low-temperature (81 K) cathodoluminescence (CL) study of ZnO nanowires bent into L- or S-shapes. The figure shows a nanowire (Fig. a) with the positions of CL measurements marked. The corresponding CL spectra-revealing a peak shift and broadening in the region of the bend-are shown in Figure b.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
135
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 142 publications
(153 citation statements)
references
References 38 publications
15
135
0
3
Order By: Relevance
“…It has been demonstrated that compressive and tensile strains will result in wi dening and narrowing bandgap in CdSe crystal, respectively. The similar conclusion has also been widely demonstrated in other semiconductors [7,[15][16][17][18]21,23,24]. Therefore, an inhomogeneous strain field imposed to CdSe crystal will induce a continuous spatial variation of electronic band structures.…”
Section: Resultssupporting
confidence: 52%
See 2 more Smart Citations
“…It has been demonstrated that compressive and tensile strains will result in wi dening and narrowing bandgap in CdSe crystal, respectively. The similar conclusion has also been widely demonstrated in other semiconductors [7,[15][16][17][18]21,23,24]. Therefore, an inhomogeneous strain field imposed to CdSe crystal will induce a continuous spatial variation of electronic band structures.…”
Section: Resultssupporting
confidence: 52%
“…In the bending region, the strain along the hexagonal axis [0001] varies linearly from compressive inside to tensile outside as ε = x/ρ where −d/2 ≤ x ≤ d/2, ρ is the local curvature radius, and d is the diameter of the nanowire. The maximum bending strains at the outer and inner edges of the curved nanowire are ε = ± d/2ρ [17,20], respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, our investigation demonstrates that the donor-bound exciton drift induced by the elastic strain gradient is the reason of the overall energetic red-shift in bent ZnO micro/ nanowires observed in all previous works. 17,20,21 …”
Section: Resultsmentioning
confidence: 99%
“…For low-dimensional materials, the effect of strain on tuning physical properties becomes enhanced when compared with their bulk counterparts owing to the broader tunable range resulted from the large elasticity when the dimension of a material is scaled down. [7][8][9][10][11][12] For example, the loadable elastic strain of nanomaterials can be approximately reached to their theoretical values, [13][14][15][16][17][18][19][20] which can be increased by 2-3 orders of magnitude higher than their bulk forms. Thus, such a huge difference for the loadable strain between the nanomaterials and their bulk counterparts may bring remarkable changes in physical properties.…”
mentioning
confidence: 99%